The Evaluation of Disaster Alert School Program (SSB) In Padang City - Oktavia, Oktavia (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research was to analyze the evaluation ofContext, Input, Prosess,Product, Outcome dand policy direction of SSB Program (Disaster Alert School) at Senior High School Pertiwi 1 which was located in the Tsunami-prone red zone area in Padang City.This research was an evaluative research and it was approached qualitatively ad quantitatively (mixed method). The researcher used purposive sampling technique to choose research participants. The participants were mento of SSB, Headmaster, KOGAMI (Tsunami Alert Community), and BPBD (Regional Disaster Management Agency). The techniques of data collection were observation, interview, questionnaire, and documentation. The results of this research are 1. Context evaluation was manifested through; (a) success goals (b) good environment condition (c) Advantages and Disadvatages of the program. 2. Input evaluation manifestations are; (a) the lack of natural resources and the necessity of relevant background of education (b) low budget (c) good facilities and infrastucture (d) time of SSB establishment in 2009 until now (e) excellent school policy in the form of sustainable development. 3. Process evaluation manifestations are; (a) a good planning between school and related institutions(b) the implemntation of routine physical and no-physical disaster based curriculum decision (c) A routine socialization and direct ad indirect socialization (d) supervising was well conducted by mentors and other related institution (e) a very good maintenance and utilization of infrastructure. 4. Product evaluation manifestations are; (a) achievement of SSb objectives (b) the formation of disaster curriculum (c) positive effects on students, teachers and schools staffs. 5. Outcome Evaluation are (a) a prositive effect on local communities. Based on CIPPO theory, there are 4 final results of the evaluation: (a) the program is dismissed (b) the program continue (c) the program is modified (d) re-programming. Based on the advantages and disadvantages of the program and its implementation in the field, it ccouldan be concluded that the program continued and was modified on its management. The policy direction form the result of AHP analysis suggested 5 policy priorities, namely (1) Creating SSB based school (2) building cooperation between SSB manager and related institution, (3) School’s coordination on facility and infrastructure development, (4) Giving SSB program training to the managers and mentors, (5) Realizing a special funds for SSb program in school.